For When It Rains: How One Community College Established an Incentivized Student Savings Account. Issue 4 (3rd April 2021) - Serna, Karen L.; Eguiluz, Linda; Taylor, Z. W.
ABSTRACT: This practice brief addresses the financial insecurity faced by many community college students and provides recommendations for community college practitioners on how to use incentivized savings accounts to teach financial literacy and prepare students for financial challenges that may impact their educational future. Despite reactive attempts at creating on-campus food pantries, financial emergency funds, and financial literacy interventions, little research has addressed how community colleges can be proactive and help students avoid a financial crisis before it begins. This paper details how a large, urban community college took a proactive approach to these concerns and developed and implemented an incentivized student savings account program. The savings program encourages students to complete financial literacy tasks in exchange for account deposits, which could be used for future unanticipated expenses. Implications for program development, financial services practice, and future research are addressed.